A TEOLOGIA E O ESTUDO DA RELIGIÃO. A hermenêutica teológica como reinterpretação da linguagem da fé e da existência cristã. - Salles, Walter Ferreira (2006)
The present work presents a reflection on the role of theology in the study of religion, in the current Brazilian university context. The main thesis of this work is based on the idea that theology, in the study of religion, must be understood as theological hermeneutic of antropological orientation, and on watching its exercise as the interpretation of the language of faith and the Christian existence.